2021
DOI: 10.1021/acs.jpcc.0c10140
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Many-Particle Phenomena in Lead Bromide Hybrid Perovskite Nanocrystals Under Strong Optical Excitation

Abstract: In recent years, there has been a surge in research efforts to utilize organic−inorganic lead halide perovskites (OLHPs) in optoelectronic devices (e.g., concentrator photovoltaics) requiring high light illumination. Yet, knowledge of the physics of photocarriers in perovskites in the high-excitation regime is limited. Here, we investigate carrier and exciton dynamics that are manifested under strong light illumination in methyl ammonium lead bromide perovskite nanocrystals (NCs) using ultrafast pump-probe spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Femtosecond broadband TA measuring system is based on a femtosecond Ti: Sapphire amplifier (wavelength ∼ 800 nm and pulse width < 35 fs). , The output from the amplifier (Spitfire Ace, Spectra physics) was divided into two components to generate pump and probe pulses. Pump pulses (at 610 and 532 nm) were obtained from the nonlinear optical parametric amplifier (TOPAS).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Femtosecond broadband TA measuring system is based on a femtosecond Ti: Sapphire amplifier (wavelength ∼ 800 nm and pulse width < 35 fs). , The output from the amplifier (Spitfire Ace, Spectra physics) was divided into two components to generate pump and probe pulses. Pump pulses (at 610 and 532 nm) were obtained from the nonlinear optical parametric amplifier (TOPAS).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Metal halide perovskites (MHP), in particular the trihalide perovskites, are a remarkable class of materials that have resulted in a rapid series of breakthroughs in the field of optoelectronic devices. [1][2][3][4][5][6] Over the past decades the MHPs have emerged as suitable materials for solar cells, light emitting diodes, lasers, transistors, and memory devices. [7][8][9][10][11][12][13] It has been demonstrated that MHP-based photovoltaic devices show power conversion efficiencies of more than 22%, [14,15] and the devices can be produced on cheap non-crystalline substrates by both vapor deposition and solution processing.…”
Section: Introductionmentioning
confidence: 99%
“…Lead halide perovskite nanocrystals (PNCs) have shown exceptional promises in light emitting devices (LEDs) due to their high photoluminescence quantum yield (PLQY), wide tunable emission wavelength range, defect tolerance, and low-cost solution processability. In the past few years, tremendous efforts such as compositional engineering (via doping and alloying), , surface reconstruction, , shape tuning, , and interfacial engineering , have been employed to fabricate efficient PNC based LEDs, which led to the significant enhancement in the external quantum efficiencies (EQEs) exceeding 20% . Even though the EQEs of PNCs are significantly enhanced, , still there are numerous complications associated with the device performances and operational stability including defects stemming from Br and Pb vacancies, detachment of ligands from the CsPbBr 3 surface, leading to a decrease in photoluminescence quantum yield (PLQY), and change of the morphology with time.…”
mentioning
confidence: 99%